Pengurangan Impor Sodium Klorat di Indonesia melalui Desain ClO2 Semi-Integrated pada Modifikasi ClO2 R8 Plant 10 Ton/Hari - Manik, Boy Jansen Roberto; Amri, Idral; Paratenta, Maria (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2024)
Pulp production always has a bleaching process that uses chlorine dioxide (ClO2) as a bleaching pulp agent. One of the ClO2 production units that are used in the Pulp Industry in Indonesia is a ClO2 R8 non-integrated plant with the process of reacting sodium chlorate, sulfuric acid, and methanol. This ClO2 production type has a weakness, especially in supplying the raw material sodium chlorate, which is needed to import, and the characteristics are easy to explode, making production costs high. This research aims to modify the ClO2 R8 non-integrated by changing to a ClO2 semi-integrated plant. In this research, HYSYS was used to simulation to get mass and energy balance and other component data, and the design of equipment based on the American Society of Mechanical Engineers (ASME), Kern, internal data company, and others to get the specification equipment and also drawn using Autocad. The last step is to account for the economic for getting cost of production before and after modification, fixed capital cost, benefit, payback period, and return on investment. The resulting area, the first, modification of the ClO2 R8 plant by changing to ClO2 semi-integrated could produce chlorate solution 510 g/l which they use electrolyzers system from Chemetics with 20 cell M25 and hypo system. Second, the cost production for the ClO2 semi-integrated plant is 1393 USD/T, the benefit is 599.79 USD/year, the Payback period (PBP) is 6,65 years with an investment of about 3988 KUSD and RoI 15%.